Thiopurines: Recent Topics and Their Role in the Treatment of Inflammatory Bowel Diseases - Tominaga, Keiichi; Sugaya, Takeshi; Tanaka, Takanao; Kanazawa, Mimari; Iijima, Makoto; Irisawa, Atsushi (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) and Crohn's disease (CD) are chronic inflammatory bowel diseases (IBD) of unknown etiology, characterized by repeated relapse and remission. The efficacy of thiopurine in IBD was first reported in the late 1960s. Thiopurines is infrequently used to induce remission in IBD, especially UC, and is more often used in conjunction with steroid reduction in steroid-dependent cases or to maintain remission. Therefore, thiopurines tend to be used long-term, but adverse events that accompany long-term use, such as lymphoproliferative disorders, must be monitored with care. On the other hand, thiopurine plays a very important role in controlling the immunogenicity of biologics. Furthermore, although thiopurine is an old drug, new findings such as the prediction of serious adverse events such as severe alopecia and acute advanced leukopenia by NUDT15 gene polymorphism analysis and the possibility of appropriate drug monitoring by detailed analysis of 6-TGN have been clarified. However, the potential for thiopurine withdrawal has not been resolved and further studies, including RCTs, are necessary to answer the clinical question of when (under what conditions) thiopurine withdrawal is possible.